The Health Effects of 14 Weeks of Physical Activity in a Real-Life Setting for Adults with Intellectual Disabilities. (1st December 2022) - Højberg, Laurits Munk; Helge, Eva Wulff; Pingel, Jessica; Wienecke, Jacob
Abstract : Background . The life expectancy of individuals with intellectual disabilities (ID) is reduced compared to the general population, and one of the main contributors to earlier death is inactivity. Aim . To investigate how 14 weeks of physical activity (PA) in a real-life setting affects cardiovascular fitness, body composition and bone health of adults with ID. Methods . Adults with ID were recruited into a PA-group ( N  = 52) or a control group (CON, N  = 14). The PA-group participated in 14 weeks of PA, and body composition, cardiovascular fitness and bone health were assessed before and after the intervention. Outcomes and Results . Cardiovascular fitness and body composition improved from pre to post within the PA-group: Heart rates (HR) during the last 30 seconds of two increments of a treadmill test, were reduced (3.2 km/h: −4.4 bpm, p < 0.05 ; 4.8 km/h: −7.5 bpm, p < 0.001 ) and fat mass was reduced (−1.02 kg, p < 0.05 ). A between-group difference in favour of the PA-group, were observed in whole body bone mineral density (BMD) (0.024 g/cm 2, p < 0.05 ). Conclusions and Implications . Fourteen weeks of PA performed in a real-life setting increased cardiovascular fitness, reduced fat mass and improved BMD in the weight-bearing skeleton in the PA-group. Increased and regular PA seems to be a promising tool to promote physical health in adults with ID.